National Incidence of Pediatric Mastoiditis in the United States, 2000–2012: Creating a Baseline for Public Health Surveillance. Issue 1 (January 2019) - King, Laura M.; Bartoces, Monina; Hersh, Adam L.; Hicks, Lauri A.; Fleming-Dutra, Katherine E.
Abstract : Between 2000 and 2012, the national estimated incidence rate of pediatric mastoiditis, a rare but serious complication of acute otitis media, was highest in 2006 (2.7/100, 000 population) and lowest in 2012 (1.8/100, 000 population). This measure provides a baseline for public health surveillance in the pneumococcal conjugate vaccine era as stewardship efforts target antibiotic use in acute otitis media. Abstract : Supplemental Digital Content is available in the text.